Diversity of Worship Fatwas During the Covid-19 Pandemic at the Institution of The Indonesian Ulama Council - Marwadi, Marwadi; Labib, Mughni (Al-'Adl, 2024)
Fatwa is an Islamic legal consideration that is conveyed by a mufti or scholar, individually or collectively and becomes an answer to questions and to respond to problems that occur in society. The MUI fatwa is a fatwa that is quite significant when the Covid-19 pandemic occurred in the world, including in Indonesia. However, the fatwa that has been issued by the Central MUI as a guideline for the Muslim community in carrying out worship activities during the Covid-19 pandemic season is not necessarily followed and socialized by the MUI institutional level at the regional level. Some of the central MUI fatwas differ from those issued by regional MUIs, such as the fatwa on holding worship at home, wavy Friday prayers, and the use of the astrazeneca vaccine. The reason for the difference between the Central MUI and the MUI is because each MUI institution has a different typology and point of view. For the same case, a different typology produces a different fatwa, as in the difference in the fatwa prohibiting congregational prayers at the mosque between the traditional thinking typology of the West Sumatra MUI and the moderate thinking typology. Likewise, different perspectives can also lead to differences in fatwas between the Central MUI and regional MUI, such as the case of the halal status of the astrazeneca vaccine between the Central MUI and the East Java MUI. The same typology of thought, namely the moderate typology, but with a different point of view produces a different fatwa. Then in the case of the fatwa prohibition of Friday prayers, the waves are more due to conditions of social change. The central MUI fatwa prohibits wavy Friday prayers because they appear under normal circumstances while the fatwa allows wavy Friday prayers because there is an outbreak of Covid-19 even though in fact both of them have a moderate typology of thinking.